Pengendalian Kualitas Crude Palm Oil (CPO) di Pabrik Kelapa Sawit Dengan Menggunakan x ̅-S Chart - M Hudori (Politeknik Kelapa Sawit Citra Widya Edukasi, 2015)
Palm oil mill (POM) must be able to produce high quality products, because it will increase value added of crude palm oil (CPO) and palm kernel (PK) as products. To maintain quality of CPO, especially FFA, the treatment of fresh fruit bunches (FFB) should be regulated. Control of the FFA is very necessary so that productivity can be maintained the POM. Poor condition of FFA will also easily identified so that it can be followed up. CPO quality control, especially FFA parameter can be done by using chart and R chart, namely by looking at the variability of the process on a daily basis. From the test result shows that the condition is so bad that the process capability need immediate corrective action to resolve the issue.